Visual results and complications of temporal incision phacoemulsification performed with the non-dominant left hand by junior ophthalmologists. Issue 11 (1st November 2002) - Kageyama, T; Yaguchi, S; Metori, Y; Chida, M; Koizumi, K; Onishi, T; Ayaki, M
Abstract : Aims: To assess the results of temporal incision phacoemulsification and aspiration performed with dominant and non-dominant hand of ophthalmology trainees. Methods: Retrospective analysis were made of 203 surgeries with dominant hand and 207 with non-dominant by five trainees at two institutions. Trainees sat at the patient's head, manipulating instruments with the dominant right hand for the right eye, and the non-dominant left hand for the left eye. Results: Vitreous loss occurred in 12 (5.9%) of 203 dominant operated eyes and seven (3.4%) of 207 non-dominant operated eyes. The rate of endothelial cell loss was 6.1% (9.8%) in dominant and 7.4% (12.4%) in non-dominant. Mean ultrasound time were 1.81 (0.70) minutes in dominant and 1.78 (0.78) minutes in non-dominant. One trainee showed statistically significant excesses in incidence of vitreous loss in dominant operated eyes (8.7%, p=0.0270), and one showed statistically significant prolongation of the operation in nondominant operated eyes (26.3 minutes, p=0.0315). In all other trainees, all parameters had no difference in both sides. Conclusions: Ophthalmology trainees could successfully learn the technique with both hands. The authors consider that the skill of the non-dominant hand may be knowledge based and that surgeons avoid mistakes by mental efforts.